An Empirical Study of the Partnership Network Structure of Automakers under CASE (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The purpose of this research is to analyse empirically the effect of the ongoing and radical change in the business environment in the automotive industry called CASE (Connected, Autonomous/Automated, Shared, Electric) on the network structure of the partnerships of automobile manufacturers. Traditionally, partnerships in the automotive industry have been dominated by dense network structures. On the other hand, according to previous studies in other industries, network structures suitable for radical innovation involve weak ties, structural holes, and betweenness centrality, etc. This study’s methodology used actual data on the partnerships of automobile manufacturers around the world which were analysed using a social network analysis method. The analysis results showed a significant correlation between the degree of approach to CASE and the number of weak ties and the size of structural holes. In addition, some case studies show significant differences in network structure between new technology venture companies and existing legacy technology companies. The discussion highlights the insight that the network structure of the automobile industry could change significantly in the future due to technological innovation. Future work should acknowledge that changes in the industry structure due to CASE are still in progress, and continuous research is needed.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.